الضغوط المهنية و علاقتها بالأداء الوظيفي لدى أساتذة الطور الابتدائي - عيشاوي, سعد الله; الصديقي, عبد الحليم (جامعة الوادي university of Eloued, 2015)
Abstract The employee or worker is considered as a basis of success of any organization through the work or effort that he can perform. This is why he was given a great importance, following his performance and the pressures that he faces during his work, in order to raise his morale. In general, the study tried to answer the following question : What's the relationship between the pressures of the work and the performance among primary school's teachers? Bo this subject is chosen because it touches one of the organization's sides and it also enters into our interest about the education sector. Its importance appears on the privacy of performance among teachers and the obstacles that face them. The most important of this study : -The special levels of the work's pressures that face the individuals of the sample differentiate between high and low whether it was the result of hardness of work, ambiguity or the conflict of the role. -The existence of correlation between the pressures of work (conflict, ambiguity or hardness of role) and the performance of teachers.
دراسة ميدانية بالمدارس الابتدائية مقاطعة المقارين – ولاية ورقلة
مذكرة ماستر علم اجتماع تخصص تنظيم وعمل
Keywords: الضغوط المهنية، المدرسة الإبتدائية، الأداء الوظيفي; Pressions professionnelles, école primaire, rendement au travail; Occupational pressures, primary school, job performance